Dilalah Jumlah Ismiyyah dan Fi'liyyah Dalam Penafsiran Al-Qur'an - Rohadi, Rohadi; Agustiar, Agustiar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to analyze the number of Ismiyyah and Fi'liyyah in the interpretation of the Qur'an. This type of research is a literature review. Data collection with documentation. Data analysis with SLR. The results of the research are that in the interpretation of the Qur'an, the concepts of the number of ismiyyah and fi'liyyah have an important role in understanding the meaning of the holy verses. Dilalah amount ismiyyah refers to the signs of nouns in Arabic that indicate number, such as singular, double and plural, while dilalah number fi'liyyah refers to the signs of verbs that indicate forms of action or time. Understanding these two concepts helps deepen the interpretation of the Qur'anic text by considering the linguistic context and sentence structure. By paying attention to the number of ismiyyah and fi'liyyah, readers can interpret the verses of the Qur'an more carefully, understand the nuances of their meaning, and gain deeper insight into the teachings and messages contained in the Islamic holy book.